Design features of a guideline implementation tool designed to increase awareness of a clinical practice guide to HIV rehabilitation: A qualitative process evaluation. Issue 4 (26th November 2018) - Salbach, Nancy M.; Solomon, Patricia; O'Brien, Kelly K.; Worthington, Catherine; Baxter, Larry; Blanchard, Georgina; Casey, Alan; Chegwidden, Will; Dolan, Le‐Ann; Eby, Sarah; Gervais, Nicole
Abstract: Rationale, aims, and objectives: A comprehensive electronic guide (e‐module) describing an interprofessional, evidence‐informed approach to HIV rehabilitation was developed as an education resource for rehabilitation professionals. We developed a guideline implementation tool, consisting of a 10‐week, case‐based education intervention delivered by email, that was perceived to increase rehabilitation professionals' (occupational therapists (OTs), physical therapists (PTs), and speech language pathologists (SLPs)) knowledge and confidence to apply best practices in HIV rehabilitation. This study aimed to increase understanding of how the design of the guideline implementation tool facilitated increased awareness of and access to the e‐module among rehabilitation professionals. Methods: We conducted a single group intervention study with rehabilitation professionals in Canada and the United Kingdom. Six case studies targeting HIV pathophysiology and associated conditions, an interprofessional approach to rehabilitation assessment and treatment, and psychosocial issues experienced by people living with HIV, were emailed to participants at 2‐week intervals. Individual semi‐structured interviews were conducted post‐intervention. Interview transcripts were analysed using a descriptive qualitative approach. Results: Twenty‐six individuals (17 from Canada, and 9 from the UK; 16 PTs, 7 OTs, 3 SLPs) were interviewed. One main theme related to design features of the intervention that facilitated learning and access to the e‐module emerged. Subthemes highlighted features of the case‐based intervention, including technical feasibility, terminology, formatting and layout, hyperlinks, number and frequency of case studies, and diverse and realistic case scenarios relevant to the learner's practice, that participants described as facilitating access to information and learning. Conclusion: Electronically administered case studies were perceived as complementary knowledge tools that increased access to an evidence‐informed guide to HIV rehabilitation. Findings provide guidance on using case studies as a guideline implementation tool to facilitate access to information and related resources to optimize learning.